Cancer Procoagulant in Acute Non Lymphoid Leukemia: Relationship of Enzyme Detection to Disease Activity - Donati, M B; Falanga, A; Consonni, R; Alessio, M G; Bassan, R; Buelli, M; Borin, L; Catani, L G; Pogliani, E; Gugliotta, L; Masera, G; Barbui, T (Thrombosis and Haemostasis, 1990)
Blast cell extracts from patients with acute non lymphoid leukemia (ANLL) express cancer procoagulant (cp). Thii factor X (FX) activator is distinct from tissue factor (TF) in that it does not require factor VII (FVII) to trigger blood coagulation, it acts as a cysteine proteinase and is not present in normal mononuclear cells. Tb assess whether there is any relationship between the presence of CP and the status of the disease, ANLL patients have been studied at diagnosis, during remission, at relapse. The procoagulant activity in either the presence or absence of F VII and sensitivity to cysteine proteinaie inhibitors were tested on cell extracts. Immunoreactivity was explored with an anti-cP polyclonal antibody. Data obtained in gL newlydiagnosed ANLL patients (subtypes M1 to M5, EAB classification) confirmed the presence of cp in M1- to M4 groups (mean + sE Fvll-independent activity: M1 = 2.1 ± 0.7 unit/mg; M2 = 5.7 ± 1.7 unit/mg; M3 = 31.5 ± 8 unit/mg M4 = 1.6 ± 1.2 unit/mg; CP was absent in the M5 type. In eight patients analy zedin a subsequent phase of partial remission, specific activity had dropped from 26.9 ± 7.8 to 10.5 ± 4.0 unit/mg. Activiiy was virtually absent (0−0.05 unit/mg) in the bone marrow of 37 patients studied at complete remission. Bone marrow samples from six subjects tested at different intervals after complete remission were repeatedly negative for CP but became positive 2 to 5 months before relapse. Upon relapse, the FVII indbpendent activity rose to 24.2 ± 8.2 unit/mg.These results suggest that CP activity may be closely associated with the presence of myeloid malignant cells in the bone marrow, a finding of potential relevance not only to the coagulation disorders of acute leukemia, but also to the early deteition of blast cells in ANLL.